2013
DOI: 10.1128/aem.03168-12
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Sublethal Injury, and Recovery of Environmental Burkholderia pseudomallei in Soil Subjected to Desiccation

Abstract: bEnvironmental Burkholderia pseudomallei isolated from sandy soil at Castle Hill, Townsville, in the dry tropic region of Queensland, Australia, was inoculated into sterile-soil laboratory microcosms subjected to variable soil moisture. Survival and sublethal injury of the B. pseudomallei strain were monitored by recovery using culture-based methods. Soil extraction buffer yielded higher recoveries as an extraction agent than sterile distilled water. B. pseudomallei was not recoverable when inoculated into des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A high moisture content (greater than 10–15–40%) has been implicated as important in enhancing the presence or survival of B . pseudomallei in soil [ 11 , 20 22 ]. Larsen and colleagues (2013) showed that prolonged survival was possible in desiccated (91 days) and intermittently irrigated soils (113 days) where the moisture content varied from close to 0% (after 14 days starting at ~8%) for the desiccated soil to approximately 5–13% in the intermittently irrigated soil.…”
Section: Discussionmentioning
confidence: 99%
“…A high moisture content (greater than 10–15–40%) has been implicated as important in enhancing the presence or survival of B . pseudomallei in soil [ 11 , 20 22 ]. Larsen and colleagues (2013) showed that prolonged survival was possible in desiccated (91 days) and intermittently irrigated soils (113 days) where the moisture content varied from close to 0% (after 14 days starting at ~8%) for the desiccated soil to approximately 5–13% in the intermittently irrigated soil.…”
Section: Discussionmentioning
confidence: 99%
“…B. pseudomallei is able to survive for long periods in moist environments, although it survives less well at low temperatures ( 15 , 16 ). Although the organism may survive desiccation, viability may be compromised ( 17 ). Therefore, clinical samples should be transported to the laboratory at room temperature and processed as soon as possible, and swabs should preferably be placed in a suitable transport medium.…”
Section: Optimal Diagnostic Workup For Patients With Suspected Melioimentioning
confidence: 99%
“…The adaptation of B. pseudomallei through morphological alterations may increase its longevity in soil, particularly in endemic areas in which the soil has physicochemical properties suitable for soil-borne pathogens. 16,17,32 Conversely, the loss of culturability and viability observed in soils with high-osmotic stress (i.e., 1.5-3% NaCl), Figure 5A and B) suggests a method of controlling the B. pseudomallei population because our results showed that B. pseudomallei lost its viability after 120 days of exposure to osmotic stress. This result confirmed our earlier findings that these conditions could be used to control bacterial numbers.…”
Section: Discussionmentioning
confidence: 78%
“…16 A study of soil microcosms demonstrated that dry soil in tropical endemic regions may act as a reservoir of B. pseudomallei during the dry season, with an increase in their number and the potential for their mobilization from the soil to water occurring during the wet season. 17 The association of the presence of B. pseudomallei with that of iron and salt in water and soil has been demonstrated in endemic areas. 16,[18][19][20][21][22] These results may facilitate understanding of the ability of B. pseudomallei to adapt to soil in northeastern Thailand that has different environmental features, including high salinity and the presence of iron.…”
Section: Introductionmentioning
confidence: 99%